CHALLENGING THE WEST BY (AB) USING THE VACUUM: THE CASE OF THE RUSSIAN INFLUENCE IN REPUBLIC OF NORTH MACEDONIA - Spasov, Aleksandar and Brsakoska Bazerkoska, Julija (Faculty of Law "Iustinianus Primus", UKIM, Skopje, 2019)
The North Atlantic Treaty Organization (NATO) enlargement since the end of the Cold War prompted a debate on several significant issues. The NATO enlargement with the Eastern European countries generated a debate over whether it contributes to worsening the relations between the West and Russia. The same dilemma is present when it comes to the NATO enlargement with the Western Balkans countries. The paper argues that since NATO failed to complete its enlargement endeavors in the Western Balkans, in the case of, then, the Republic of Macedonia,1 during the 2008 Bucharest Summit, it opened the scene for Russian influence. The case of Republic of North Macedonia (N. Macedonia) is examined in details in order to support the above stated premise. However, the paper argues that the Russian influence on the Balkans is not necessarily through military means. On the contrary, the paradigm has shifted and Russia is (ab) using the vacuum that has been left by NATO in the Western Balkan. This vacuum was created mainly because of the shift of NATO’s focus from Europe to Central Asia and Middle East. In this newly created situation, the Western Balkan’s countries which are weak democracies and lack stable institutions are influenced by Russia, which is projecting its influence through means of oil and gas industry, penetration in the banking sector and renewal of the sense for belonging to the same Slavic and Orthodox community.
Keywords: Western Balkans, Russia, Republic of North Macedonia, NATO, NATO enlargement